Post COVID‐19 Cerebral Venous Thrombosis presenting as Acute Dementia. (20th December 2022) - Dubey, Shubham; Dubey, Ayush
Abstract: Background: Coronavirus disease (COVID‐19) is an infectious disease caused by SARS‐CoV‐2 virus which may lead to various neurological complications as reported in the literature. One important complication is CVT (Cerebral Venous Thrombosis) which classically presents as acute headache, seizures and focal neurological deficits. We report an interesting and rare case presentation of CVT here. Method: A 32 year old female presented to ER with history of progressive forgetfulness since 4 days. She had difficulty in remembering recent activities and names of close associates. This was followed by holocranial headache after 2 days. She had history of COVID‐19 infection 20 days before the symptom onset. With the suspicion of acute vascular event, she was subjected to brain imaging. Result: MRI brain with MR venogram showed left temporal venous infarct along with left transverse sinus and superior sagittal sinus thrombosis. She was treated with heparin and acenocoumarol subsequently along with supportive care with full relief in her symptoms. Conclusion: CVT is now a known complication of COVID‐19 infection. It is generally an acute condition presenting with its classical features. However, it can also rarely present with other manifestations like acute cognitive decline or rapidly progressive dementia. Careful approach towards clinical presentation with appropriate diagnostic testing can quickly identify this condition for proper and timely treatment.